Malignant transformation of calcifying epithelial odontogenic tumour with solitary pulmonary metastasis. Issue 12 (December 2021) - Tabaksert, A.S.; Jenkins, G.; Sloan, P.; Adams, J.
Abstract: This report describes the management of a case of calcifying epithelial odontogenic tumour (CEOT) that underwent malignant transformation and metastasized to the lung. The solitary pulmonary metastasis was discovered incidentally on computed tomography (CT) imaging of the neck. It appears that only one previous case with proven pulmonary metastasis has been reported in the literature, which involved multiple pulmonary deposits managed with platinum chemotherapy. The long-term prognosis of metastatic CEOT is therefore unknown. In the case presented here, the patient was managed successfully with surgery alone. There is often diagnostic uncertainty because histological features of benign, recurrent, and malignant CEOT are not dissimilar. Ki-67 immunohistochemistry is helpful, as higher levels are more indicative of malignancy. We consider that in cases of suspected recurrent and malignant CEOT, CT imaging of the thorax and abdomen as part of follow-up may identify metastases early, resulting in earlier treatment, an improved prognosis, and reduced morbidity and mortality.